Enzootic bovine leucosis (Veterinary Science, 2017)
Enzootic bovine leucosis is a chronic, viral and contagious disease of adult cattle, with higher incidence in dairy production. It is characterized by asymptomatic presentations, persistent linfocitosis and linfosarcomatosis. Its importance lies in the limitations it causes for the export of livestock, semen and embryos, the direct and indirect economic losses, and in addition, this disease has recently begun to consider potentially a zoonotic one. The objective of this paper is to conduct a review of the knowledge about this disease, including progress on the different available diagnostic techniques.
Keywords: Sarcoma; Enzootic bovine leukosis; Linfosarcomatosis